2016
DOI: 10.1007/s13555-016-0153-2
|View full text |Cite
|
Sign up to set email alerts
|

Under-Treatment of Patients with Moderate to Severe Psoriasis in the United States: Analysis of Medication Usage with Health Plan Data

Abstract: IntroductionPsoriasis is a chronic inflammatory disorder with significant morbidity and mortality, but a persistent gap appears to exist for the adequate treatment of patients with moderate to severe disease. As the extent of under-treatment is unknown, we attempted to determine overall treatment patterns and estimate under-treatment using a large database.MethodsData from the US National Health and Wellness Survey was used to estimate the proportion of patients with mild, moderate or severe psoriasis. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 15 publications
2
46
1
Order By: Relevance
“…Studies have indicated that 20-32% of patients with moderate-to-severe psoriasis are not receiving any therapy, 26,27 and undertreatment is common, with substantial proportions of moderate (19-30%) and severe (22-33%) psoriasis patients receiving topical treatments only. This statistic underscores the variability in psoriasis care delivery among healthcare providers and potential knowledge or access gaps that need to be addressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have indicated that 20-32% of patients with moderate-to-severe psoriasis are not receiving any therapy, 26,27 and undertreatment is common, with substantial proportions of moderate (19-30%) and severe (22-33%) psoriasis patients receiving topical treatments only. This statistic underscores the variability in psoriasis care delivery among healthcare providers and potential knowledge or access gaps that need to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulty that patients reported in finding effective therapy is consistent with recent data on the suboptimal treatment of psoriasis. Studies have indicated that 20-32% of patients with moderate-to-severe psoriasis are not receiving any therapy, 26,27 and undertreatment is common, with substantial proportions of moderate (19-30%) and severe (22-33%) psoriasis patients receiving topical treatments only. 14,27 High proportions of survey respondents indicated that their disease resulted in discrimination or humiliation in daily life and negative consequences for work and personal relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis is a chronic, relapsing, and systemic inflammatory skin disease that affects approximately 7.4 million adults in the United States (US) (1), with plaque psoriasis accounting for more than 80% of cases (2). According to an estimation based on data from the US National Health and Wellness Survey from 2007 to 2012, 1.7 million insured US patients have moderate-tosevere plaque psoriasis (3). Moderate-to-severe psoriasis is associated with a considerable disease burden, affecting patients' physical and psychological wellbeing and resulting in reduced quality of life and work productivity (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Significant barriers exist that often lead to undertreatment of many patients with moderate psoriasis, with resulting unsatisfactory clinical outcomes (1)(2)(3)(4)(5). Of importance, there appears to be a lack of consensus on how to identify and appropriately treat patients with moderate psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, treatment strategies that specifically address the needs of patients with moderate psoriasis have not been developed. Most patients with moderate psoriasis or moderate to severe psoriasis continue to receive no therapy or topical treatments alone, despite lack of symptom relief (1,2,5).…”
Section: Introductionmentioning
confidence: 99%